Anatomy & physiology revealed 3.0 an interactive cadaver dissection experience (Ohio : McGraw-Hill, 2011)
Cadaver photos blended with a layering technique reveal more than 5,000 anatomical structures. Program includes dissection, animation of anatomical structures and physiological processes, histology, imaging, and quizzes and simulated practical exams. Includes all body systems: integumentary, skeletal, muscular, nervous, endocrine, cardiovascular, respiratory, lymphatic, digestive, urinary, and reproductive. Three new content modules for 3.0 are body orientation, cells & chemistry, and tissues.
Title from container
System requirements (PC): Windows XP/Vista/7, Pentium II 500 MHz processor; 128MB RAM; Java 1.4.2 or higher (free download); 1024 x 768 pixel screen resolution, color monitor running'Thousands of colors' or higher; audio capable system with speakers/headphones; 8X or faster DVD-ROM drive; mouse.
Keywords: Human anatomy; Human physiology; Anatomy; Physiology